ANALISIS FAKTOR-FAKTOR YANG MENENTUKAN KEPUTUSAN PEMBERIAN KREDIT UNTUK USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) PADA LEMBAGA PEMBIAYAAN PEER TO PEER LENDING (Studi Kasus pada Koinworks Financial Technology 2019) - Andre Novian Megantara (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
The objective of this research is to analyze factors influencing the approval loans for MSMEs in the peer-to-peer lending platform. This research identifies the influence of the age of debtor, sex of debtor, length of business, loan purposes, term loan, credit scores, business turnover, leverage ratio, and loan amount as the variables of this research. Moreover, the quantitative method used in this research within the data of obtained from koinworks.com, as a Peer to Peer Lending service provider. The purposive sampling method was used resulting in 45 MSMEs that were selected as the samples and also the logistic regression analysis with IBM SPSS Statistics 24 was also used to analyze the data. The results of this research show that the sex a of debtor, credit scores, business turnover, and loan amount have positive and significant influences on the extension of credit decisions. In addition, the age of a debtor, length of business, loan purpose, term loan, and leverage ratio insignificantly influences the loan extension of credit decisions on the peer-to-peer lending institutions for MSMEs. Keywords : Peer-to-Peer Lending, MSMEs, Logistic Regression